3D printing model of the intrahepatic vessels for navigation during anatomical resection of hepatocellular carcinoma. (2017) - Kuroda, Shintaro; Kobayashi, Tsuyoshi; Ohdan, Hideki
Highlights: 3D printing models were produced for anatomical hepatectomy. It contributed our understanding of the positional relationships of tumor and vessel. It also contributed common understanding between operator and assistant during operation. Abstract: Introduction: The 3D printing model of the intrahepatic vessels and regional anatomy are often used for navigation surgery. Here, we report the use of the model for anatomical resection of hepatocellular carcinoma. Presentation of case: Case 1: A tumor, 31 mm in diameter, was located in segment 7 of the liver. Using the 3D model, we identified the regional Glissonian pedicle and performed resection of segment 7. Case 2: The tumor was located in segment 4/8 and involved the middle hepatic vein. Radical resection of segment 4 and of the ventral area of the right anterior section was performed using the 3D model. Discussion: The positional relationship between the intrahepatic vessels and liver tumors is the most important factor for anatomical resection for hepatocellular carcinoma. Therefore our simplified 3D model of intrahepatic vessels without liver parenchyma is sufficient for effective guidance during surgery and has the advantage of being feasible to use for all HCC surgeries. Conclusion: Use of 3D printed models might have many merits and contribute to the great improvement of the surgical quality.